SEPIC converter in discontinuous conduction mode: Small signal modeling and analysis. (23rd October 2021) - Agrawal, Amit; Shrivastava, Ashish; Singh, Kulwant; Mahato, Bidyut; Tiwari, Shubham; Rai, Amit
Abstract: In this article, a new approach is applied to solve the small signal state space average (SSA) model for pulse width modulated (PWM) single ended primary inductor converter (SEPIC) under discontinuous conduction mode (DCM) of operation. Authors proposed a novel approach to get duty ratio constrains that is based on variation of current in inductor. The approach used a unique correction matrix ( M ) in the modeling process and obtained better results for DCM. To demonstrate the whole technique, the SEPIC‐based power supply of 75 W is designed and system loop gain is derived with the help of this new technique. The frequency response of the proposed system is captured with the help of linearization technique using MATLAB Simulink platform. The frequency plot from the proposed techniques is much closer to simulation results as compared to conventional method. This claims high predictions for dc–dc converter operating in DCM with wide range of input supply. The proposed model is analyzed with previous SSA small signal modeling for comparative results on the basis of frequency analysis and stability. The experiment results of designed power supply have shown good power quality performance at 220‐V AC mains for light‐emitting diode (LED) lighting application. Abstract : A generalized small signal modeling technique is proposed for higher order PWM converter operating in DCM. It is based on the state space analysis with a correction matrix ( M ) and a new duty ratio constraint. The system loop gain is derived mathematically with the help of presented approach and the frequency response is captured with the help of MATLAB Simulink. The experiment results of designed power supply have shown stability with good power quality performance at 220‐V AC mains.